1990
DOI: 10.1007/bf01971830
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity of lead acetate to female rabbits after chronic subcutaneous administration. 1. Biochemical and clinical effects

Abstract: The effect of chronic subcutaneous administration of lead acetate was studied in female rabbits. The low-dose group (15 animals) received three times a week 0.10-0.20 microgram/kg body weight and the high-dose group (15 animals) 0.80-1.20 micrograms/kg. The control group received the vehicle only. Concentrations of lead in blood in the low-dose group increased to ca. 400 micrograms/l after 70 days and in the high-dose group to ca. 900 micrograms/l after 110 days. After 7.5 months eight animals of each group we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…Also, tissue hypoxia is a possible mechanism for high production of RBCs in moderate lead poisoning. MCV and MCH levels were decreased after lead intoxication in our study that it was in agreement with several studies (Noori et al;Falke & Zwennis, 1990;Antonowicz et al, 1991).…”
Section: Discussionsupporting
confidence: 94%
“…Also, tissue hypoxia is a possible mechanism for high production of RBCs in moderate lead poisoning. MCV and MCH levels were decreased after lead intoxication in our study that it was in agreement with several studies (Noori et al;Falke & Zwennis, 1990;Antonowicz et al, 1991).…”
Section: Discussionsupporting
confidence: 94%
“…These results agreed with studies conducted by Shehata () who found that the final body weight, daily body gain and FI were decreased in rabbits exposed to 0.5% lead acetate in the diet of growing rabbit. Additionally, Falke and Zwennis () reported that addition of lead at dose of 0.8–1.20 μg/kg body weight three times a week, decrease the body weight of female rabbit.…”
Section: Resultsmentioning
confidence: 99%
“…[24][25][26][27][28][29] Hg, 30,31) Pb, [30][31][32][33][34] Be 35) and Ni 7) are also able to reduce the hepatic enzyme activities. Based on those findings and our new results, the organ specificities shown by liver and lung in the susceptibilities of drug-metabolizing enzymes to several heavy metals were attributable partly, if not entirely, to the organ specific nature of enzymes.…”
Section: Fig 5 In Vitro Effects Of Heavy Metals On the Udp-glucuronylmentioning
confidence: 99%